2012
DOI: 10.1021/np300377b
|View full text |Cite
|
Sign up to set email alerts
|

Meroterpenoid and Diphenyl Ether Derivatives from Penicillium sp. MA-37, a Fungus Isolated from Marine Mangrove Rhizospheric Soil

Abstract: Penicillium sp. MA-37, which was obtained from the rhizospheric soil of the mangrove plant Bruguiera gymnorrhiza, exhibited different chemical profiles in static and shaken fermentation modes. Three new meroterpenoid derivatives, 4,25-dehydrominiolutelide B (1), 4,25-dehydro-22-deoxyminiolutelide B (2), and isominiolutelide A (3), together with three known ones were characterized from its static fermentation, while three new diphenyl ether derivatives, namely, Δ(1('),3('))-1'-dehydroxypenicillide (4), 7-O-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
63
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 20 publications
1
63
0
2
Order By: Relevance
“…[10,11], Leathesia nana [12], Phyllanthus atropurpureus [13], Symphyocladia latiuscula [14], and so on. Diphenyl ethers exhibit a wide range of interesting biological activities, such as antimicrobial [1,3,6,8,10], cytotoxic [2,6,9], radical-scavenging [11], enzyme inhibitory [5], actin inhibitory [15], anti-HSV-1 [2], and phytocidal activities [16,17]. In early chemical investigation, we reported the isolation of two diphenyl ethers, 2-isopentenyldiorcinol (9) and diorcinol (10), from a strain of endolichenic fungus Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,11], Leathesia nana [12], Phyllanthus atropurpureus [13], Symphyocladia latiuscula [14], and so on. Diphenyl ethers exhibit a wide range of interesting biological activities, such as antimicrobial [1,3,6,8,10], cytotoxic [2,6,9], radical-scavenging [11], enzyme inhibitory [5], actin inhibitory [15], anti-HSV-1 [2], and phytocidal activities [16,17]. In early chemical investigation, we reported the isolation of two diphenyl ethers, 2-isopentenyldiorcinol (9) and diorcinol (10), from a strain of endolichenic fungus Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent bioactive screening, diorcinol (10) showed significant Aβ 42 aggregation inhibitory activity with IC 50 value of 20.1 μM, while 2-isopentenyldiorcinol (9) was inactive. It is firstly discovered that diorcinol (10) with the character of diphenyl ether structure has anti-Aβ 42 aggregation activity. However, not all of diphenyl ethers displayed anti-Aβ 42 aggregation activity.…”
Section: Introductionmentioning
confidence: 99%
“…1), have played an important role in the field of agrochemicals, 6,7) can inhibit the growth of pathogenic fungi and can cause their eventual death by interfering with the respiration of the pathogen. 8,9) In our previous research, many substituted diphenyl ether derivatives were synthesized and found to have good antimicrobial activities, 10,11) and many natural diphenyl ether derivatives also elicited pharmacologically powerful activities, [12][13][14] such as antifungal, antibiotic, antimitotic and immunosuppressive activities. [15][16][17] Hence, whether the amide derivatives containing a diphenyl ether moiety will have good bioactivities is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, marine-derived fungi have triggered our interest, due to their ability to produce structurally interesting bioactive secondary metabolites [5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%